MEDIA, YOUTH AND SOCIOCULTURAL TRANSITIONS IN MALAYALAM NEW WAVE CINEMA - S. Jayan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines the evolution of Malayalam cinema from its mid-20th century literary-auteur renaissance to the contemporary “new generation” and “new wave” movements shaped by globalization and digital technologies. Drawing on a historical overview and in-depth analyses of four emblematic films, “Traffic” (2011), “Chaappa Kurishu” (2011), “22 Female Kottayam” (2012) and “Trivandrum Lodge” (2012), it explores how filmmakers deploy ensemble narratives, new-media aesthetics, and participatory promotional networks to articulate Kerala’s youth culture. The study also considers integrated marketing strategies in an era of media convergence and engages with critical counterpoints concerning spectacle, audience alienation, and the objectification of women. Findings reveal that while new wave cinema has democratized reception through social media and online platforms, it simultaneously risks reinforcing commercial spectacle and problematic gender representations. In addition to outlining ideas for future research on regional film industries navigating local customs and international pressures, the paper ends by arguing for a balanced approach that maintains cinema’s social critique and ethical imperatives alongside formal and technological innovation.